The Influence of Work-Life Balance, Employee Commitment, and Organisational Culture on the Performance of Healthcare Workers: A Case Study at Bhayangkara AKPOL Hospital - Sakuan, Gerilda Akbar; Nurmiyati, Nurmiyati; Rakhman, Muhammad Arif (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Health worker performance is a key factor in ensuring the quality of hospital services, especially in institutions with high workloads and strict operational standards. A decline in health worker performance can directly affect service quality and organisational image, requiring empirical studies to identify the factors that influence it. This study aims to analyse the influence of work–life balance, employee engagement, and organisational culture on the performance of healthcare workers at Bhayangkara AKPOL Hospital. This study uses a quantitative, explanatory design. The study population consists of all healthcare workers currently working at Bhayangkara AKPOL Hospital, and sampling is conducted using the census method, so the entire population serves as the study sample. Data were collected using a structured questionnaire with a Likert scale and analysed using simple and multiple linear regression in SPSS. The results showed that work–life balance and organisational culture had a positive and significant effect on the performance of healthcare workers. In contrast, employee engagement did not have a significant partial impact. Simultaneously, all three variables had a significant effect on healthcare workers' performance. These findings highlight the importance of managing work–life balance and strengthening organisational culture as managerial strategies for sustainably improving healthcare workers' performance.